Heart Model A.I. Three-Dimensional Echocardiographic Evaluation of Left Ventricular Function and Parameter Setting - Xing YY (Dove Medical Press, 2021)
Yuan-Yuan Xing,1,2 Hong-Yuan Xue,2 Yu-Quan Ye1,2 1Hebei Medical University, Shijiazhuang, Hebei, 050017, People’s Republic of China; 2Department of Ultrasound, Hebei General Hospital, Shijiazhuang, 050051, Hebei, People’s Republic of ChinaCorrespondence: Yu-Quan YeDepartment of Ultrasound, Hebei General Hospital No. 348 Heping West Road, Shijiazhuang, Hebei, 050051, People’s Republic of ChinaEmail yuquanyeyy@163.comObjective: This study aims to explore the feasibility of HeartModel A.I. (HM) three-dimensional echocardiography (3DE) to assess left ventricular function and discover suitable border parameter settings.Methods: A total of 113 patients that underwent echocardiography in our hospital were eligible for inclusion. The HM 3DE (HM method) and conventional 3DE (3D method) were used to analyze echocardiography images. The HM was set to different border settings (end-diastolic [ED] and end-systolic [ES] settings) to assess different left ventricular systolic function parameters including left ventricular end diastolic volume (LVEDV), left ventricular end systolic volume (LVESV), and left ventricular ejection fraction (LVEF), and left ventricular diastolic function parameters including maximal left atrium volume (LAVMAX). All of these parameters were evaluated using the HM method and then compared with the 3D method.Results: The differences in LVEDV, LVESV, and LVEF measured with different HM border settings were statistically significant (P< 0.05) and were strongly correlated with the 3D method. For LVEF, the reading using the HM method with ED and ES = 70 and 30 showed the best agreement with the 3D method, and the difference in the readings was not statistically significant (P > 0.05). For LVEDV and LVESV, the reading using the HM method with ED and ES = 40 and 20 showed the best agreement with the 3D method, but the difference in the readings was statistically significant (P < 0.05). The measurements taken using the HM method were more reproducible than those taken using the 3D method (P< 0.05). The measurement time when using the HM method was significantly less than the 3D method (P< 0.05). In terms of LAVMAX, the correlation between the HM and 3D methods was strong, but the requirements for agreement were not satisfied.Conclusion: Evaluation of the left ventricular function using HM 3DE is feasible, saves time, and is reproducible. To assess the left ventricular function, the border parameter setting of ED and ES = 70 and 30 provided the best fit for the Chinese population.Keywords: three-dimensional echocardiography, endocardial border delineation, left ventricular function, left ventricular volume